Biết rằng :bz-cy/a=cx-az/b=ay-bx/c. Chứng minh rằng x:y:z=a:b:c
biết rằng bz-cy/a = cx-az/b = ay-bx/c
chứng minh x:y:z = a:b:c
1) biết rằng :
bz- cy/a = cx-az/b= ay- bx/c
Chứng minh x:y:z= a:b:c
bz-cy/a=cx-az/b=ay-bx/c
chứng minh rằng x:y:z=a:b:c
Biết rằng : \(\frac{bz-cy}{a}=\frac{cx-az}{b}=\frac{ay-bx}{c}\) hãy chứng minh x:y:z=a:b:c
cho bz-cy/a = cx-az/b = ay-bx/c . chứng minh x:y:z = a:b:c
cho bz-cy/a = cx-az/b = ay-bx/c . CM : x:y:z = a:b:c
Biết rằng : \(\frac{bz-cy}{a}=\frac{cx-az}{b}=\frac{ay-bx}{c}\)
Hãy CM x:y:z=a:b:c
Biết rằng: \(\frac{bz-cy}{a}=\frac{cx-az}{b}=\frac{ay-bx}{c}\)
Hãy chứng minh \(x:y:z=a:b:c\)